What Factors Affect the Attractiveness of Nursing Profession? - Mari Salminen-Tuomaala (Athens Journal of Health and Medical Sciences)
Effective measures are required to mitigate the persisting nursing staff shortage. The identification of factors for choosing the profession is important for planning recruitment strategies. This study presents nursing students’ perceptions of factors that had influenced their decision to apply for the nursing program. Data was collected in March 2022 from 94 first, second and third-year nursing students in Finland. The qualitative data was analyzed using inductive content analysis. Factors that could make nursing more appealing: 1. Advancing the role of nursing at the level of individuals, organizations, and society 2. Meaningful nursing duties 3. More influence over one's work 4. Better working conditions and well-being at work 5. Development of nursing leadership 6. Work and career advancement Factors that can decrease the appeal of the nursing profession: 1. Decreased appreciation of nursing within the profession and in society 2. Mismatch salary vs. demanding workload and working conditions 3. Mismatch between staff resourcing and workload 4. Lack of support and encouragement from leaders 5. Working atmosphere detrimental to psychological well-being It is essential to invest in promoting the image of nursing at the level of individuals, organizations and society and to support nurses’ occupational wellbeing and career pathways.